PENGEMBANGAN E-MODUL MUATAN LOKAL BERBASIS FLIPBOOK UNTUK MENINGKATKAN KARAKTER BERAKHLAK MULIA PADA SISWA SD DI KABUPATEN TANGERANG - Mina Rabiatul Asiah; Sholeh Hidayat; Lukman Nulhakim (Postgraduate, University of Mataram, 2025)
This study aimed to develop a flipbook-based e-module that integrates Ketangerangan local wisdom to enhance cultural education for Phase A elementary students in Tangerang Regency. The Ketangerangan culture encompasses various traditional values, including egalitarian language (basa egaliter), etiquette (tatakrama), traditional games, and local arts. Utilizing the 4-D development model (Define, Design, Develop, Disseminate), the research focused on designing an engaging and pedagogically sound digital module. Practicality testing was conducted with 20 students and 20 teachers in Kelapa Dua District using structured questionnaires. Results showed high practicality scores—86.50% from students and 93.07% from teachers—placing the e-module in the “very practical” category. Students found the module easy to use and effective for understanding cultural material, while teachers praised its instructional quality and technical usability. The flipbook format successfully bridged the gap between technology and tradition, offering an innovative educational tool for cultural preservation and identity development. The study demonstrates that digital media, when thoughtfully designed and culturally contextualized, can revitalize local wisdom education and support its sustainable transmission to younger generations